Perceptions, experiences and barriers to accessing cervical cancer screening by women at clinics in the Greater Giyani Municipality, Limpopo Province, South Africa - Chabalala, Thembi Victoria (My University, 2024)
Background Cervical cancer remains a significant health issue worldwide, despite the availability of effective screening methods. The Health Department of South Africa provided a nationwide program for screening cervical cancer. The aim was to achieve a projected 70% rate of coverage for cancer of the cervix screening. However, up to date, only 13.6% coverage has been reached, yet the cervical cancer mortality rate is still high (Vhuromu, Goon, Maputle, Lebese, & Okafor, 2017). Furthermore, it has been observed that in Greater Giyani Municipality under Mopani District located in Limpopo Province, from 2018 up to 2020, statistics have reported only 47% cervical cancer screening uptake from twenty-six clinics, and that is significantly low (Mopani District Municipality, 2020). Aim The aim of the study was to explore perceptions, experiences and barriers to accessing cervical cancer screening services at clinics in the Greater Giyani Municipality, Limpopo Province, South Africa. Methodology This is a qualitative study which is exploratory and descriptive in nature. The population are women aged 30 years and older at clinics in the Greater Giyani Municipality. The semi-structured, in-depth, and face-to-face individual interviews were conducted using an interview guide. Tesch’s open-coding method was used to analyse the findings. Results The study revealed that most women in the greater Giyani Municipality lack knowledge about the causes, symptoms, testing procedures and prevention of cervical cancer. Despite this, women generally have a positive attitude towards the importance of cervical cancer screening and perceive themselves to be at risk. Barriers to accessing screening services include limited knowledge, difficulties in receiving results, fear of outcomes and long waiting times. Conclusion However, perceptions towards cervical cancer screening were optimistic, knowledge of study participants was poor. To improve cervical cancer screening, effort should be focused on reducing identified barriers and enhancing facilitators.
Thesis (MPH.) -- University of Limpopo, 2024
Keywords: Cancer; Cervix uteri -- Cancer; Pap test